Observing UK Bonfire Night pollution from space: analysis of atmospheric aerosol. (8th November 2016) - Pope, R. J.; Marshall, A. M.; O'Kane, B. O.
Abstract : UK Bonfire Night (BFN) is an annual event on 5 November which celebrates the failed 'gunpowder plot' of Guy Fawkes, who intended to blow up the Houses of Parliament. This event is celebrated with firework and bonfire displays, which reduce visibility and increase air pollutant concentrations. A two‐ to four‐fold increase in particulate matter concentrations was seen at some surface monitoring sites. Satellite measurements of aerosol optical depth found increases of 10–90% between days before and after BFN.